LITERARY DISTANCE ON THE U.S.-MEXICAN BORDER (Andamios, Revista de Investigación Social, 2008)
This article seeks to establish the differences that exist between Chicano writing and border writing taking as elements of analysis discourse/performance and the urban phenomenon, respectively, with the intention of promoting the literary work that develops on the U.S.- Mexican border.
Keywords: Chicano writing; border writing; discourse performance; urban phenomenon; comparative analysis